Quality management introduction to total quality management for production, processing, and services - Goetsch, David L.; Davis, Stanley 1931- (Prentice Hall, 2000)
This easy-to-use book gives future managers, engineers, technologists and technicians both the tools and know-how to guide an organization to world-class quality and competitiveness. Straightforward in approach, it helps readers understand both the "big picture" behind Total Quality Management as well as its individual elements, and readily applies theories and principles to the real world today. Organized into two part: quality management's philosophy and concepts; and tools and techniques. Examines global integration and Asian economic trends; the future of quality management; revolutionary thinking in strategic planning; beliefs vs. behavior and why they are often different; global partnering and education/business partnerships; value perception and customer loyalty; problem-solving in a total-quality setting, and much more. For anyone interested in learning more about quality management.